The Role of Family, Self Concepts and Juvenile Delinquency in Bangkalan Regency - Anis Nur Laili; Elliyati Faridah; Ali Madinah (Aloha International Journal of Health Advancement (AIJHA), 2019)
Juvenile delinquency is an act of some teenagers who are in conflict with the law, religion, and norms of society, consequently can harm others, disrupt public tranquility and also damage themselves. This is caused by factors in the child itself (self-concept), factors in society, factors from school and factors in the household or family itself and peer pressure. This study aims to explain the relationship between the role of family (parents) and self-concept with juvenile delinquency in Bangkalan District. The study design used explanatory survey method with cross sectional design. The population was all of students in Bangkalan District 2 Vocational High School class XI and XII in July 2018 as many as 315 people. The sample in the study were 100 people with a simple random sampling technique. Data was taken using questionnaires and processed by logistic regression statistical test. The results of the study showed that there was a relationship between the role of parents of sub-variables of care with ordinary juvenile delinquency, leading to violations and crimes and delinquency specifically for adolescents (p-value ≤ 0.05). There was a relationship between the role of foster parents and ordinary delinquency (p-value ≤ 0.05), but there was no relationship between the role of foster parents and juvenile delinquency. There was a relationship between self-concept (self-image, self-view and feelings of self with juvenile delinquency leading to violations, crime and there is a relationship between self-concept (self-image, self-view and self-feeling with special delinquency. The advice is that parents should pay more attention and give affection and control friends who are teenagers (their children), teenagers should often participate in youth activities, become members of youth mosques, participate in sports associations and so on to have a better self-concept. Keywords: Role of parents, Self-concept, Juvenile delinquency